2016
DOI: 10.1113/jp272177
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of a broad histamine footprint on the human exercise transcriptome

Abstract: Key pointsr Histamine is a primordial signalling molecule, capable of activating cells in an autocrine or paracrine fashion via specific cell surface receptors, in a variety of pathways that probably predate its more recent role in innate and adaptive immunity.r Although histamine is normally associated with pathological conditions or allergic and anaphylactic reactions, it may contribute beneficially to the normal changes that occur within skeletal muscle during the recovery from exercise.r We show that the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 63 publications
2
29
0
Order By: Relevance
“…Post-exercise inflammation has been associated with an elevation of neural growth factor (NGF) and glial derived nerve factor (GDNF), which likely contribute to the sensitization of Type III and IV afferent fibers in skeletal muscle (23, 35). Consistent with this possibility, these two transcripts were among the many that exhibited reduced expression at 3 h post-exercise in individuals taking combined histamine H 1 /H 2 -receptor antagonists relative to control conditions (33). This intriguing finding may explain part of the reduced pain sensitization and preservation of strength reported by Ely et al (12).…”
Section: Physiology Of Histamine During and After Exercisementioning
confidence: 79%
See 2 more Smart Citations
“…Post-exercise inflammation has been associated with an elevation of neural growth factor (NGF) and glial derived nerve factor (GDNF), which likely contribute to the sensitization of Type III and IV afferent fibers in skeletal muscle (23, 35). Consistent with this possibility, these two transcripts were among the many that exhibited reduced expression at 3 h post-exercise in individuals taking combined histamine H 1 /H 2 -receptor antagonists relative to control conditions (33). This intriguing finding may explain part of the reduced pain sensitization and preservation of strength reported by Ely et al (12).…”
Section: Physiology Of Histamine During and After Exercisementioning
confidence: 79%
“…Muscle samples taken at different time points over the course of the exercise protocol suggest that the increase in skeletal muscle HDC varies with time (14). Similarly, Romero et al (33) found that HDC expression in skeletal muscle tissue increased after exercise in humans. In mice subjected to repeated bouts of walking, however, the exercise-induced increase in HDC expression in skeletal muscle tissue was reduced, perhaps due to a training adaptation (14).…”
Section: Source Of Histamine In Exercise Responsesmentioning
confidence: 81%
See 1 more Smart Citation
“…9,10) In humans, histamine H1-and H2-receptors have been shown to be involved in mediating post-exercise hyperemia and vasodilation in skeletal muscles. 11,12) These findings suggested that histamine might support PMW by maintaining or enhancing the functions of the microcirculation.…”
Section: -3)mentioning
confidence: 90%
“…8) Recent studies suggest that histamine may play important physiological roles in skeletal muscles. [9][10][11][12] Interestingly, PMW induces HDC in skeletal muscles in mice. [13][14][15][16] However, published histological analyses of such HDC induction are lacking because appropriate anti-HDC antibodies have not previously been available.…”
mentioning
confidence: 97%